Análisis bibliográfico de los artículos publicados en medicina veterinaria y zootecnia en Colombia, 2000-2009 (2011)
The aim of this study was to analyze the bibliographic production in the area of veterinary medicine and animal husbandry in Colombia during the period 2000-2009. A literature search was conducted in the journals categories A1, A2, B and C from Colciencias Publindex classification, the journals were: Colombian Journal of Animal science, Journal Mvz Cordoba, Livestock Research Online Journal for Rural Development, Corpoica Journal-Agricultural science and Technology, Journal U.D.C.A. Current & scientific Disclosure, Journal of veterinary Medicine University of La salle, Journal of the Faculty of veterinary Medicine and Animal Husbandry National University of Bogotá, Journal of Medicine and veterinary CEs, Orinoquia Journal. We found a total of 2,644 articles published. Animal husbandry in Colombia holds a third of the published literature, the bovine specie is the most studied, followed by aquaculture. In pets, canine species occupied the first place. Another area highlighted was the zoonosis. Wildlife was found in a small percentage of manuscripts. Universities with more articles published were: University of Antioquia, University of Applied sciences UDCA, National University of Colombia, Bogotá, University of Cordoba and University of Los Llanos. This is the first study that analyzes the articles published in the area of veterinary medicine and animal husbandry in Colombia. 75% of the manuscripts of the veterinary medicine subject were carried out by public entities.